Language learning styles of ESL learners in English classrooms in Technology College of Sarawak, Kuching / Nini Lenta Anak Peter Ballak - Peter Ballak, Nini Lenta (2015)
Learners’ proficiency levels and its relationship with the preferred learning styles are unique and can influence the way the individual deal with the second language and it can become a successful factor of the language acquisition. This study investigated on the learners’ preferred learning styles according to their proficiency levels based on the grades obtained in SPM (Sijil Pelajaran Malaysia) for English language subject. Besides that, it also investigated the relationship between learners’ proficiency levels in English subject with the choice of the preferred learning styles. The study was participated by 200 Semester 2 students of Technology College of Sarawak (TCS) who are currently taking subject of English for Academic Study ULAB 1022). Data was gathered using a modified questionnaire adapted from Ehrman & Leaver Self-Questionnaire (2002) on Ectenic and Synoptic Language Learning Theory. The results indicated a weak and negative relationship between learners’ proficiency levels and the choice of the learning styles. The findings revealed that both factors were isolated factors which did not affect one another. On a further analysis, it was found that majority of learners were classified under Synoptic category, followed by Ectenic category and finally category of learners that possessed both characteristics of Ectenic and Synoptic. In terms of the pedagogical methods and learning materials, educators should redesign and implement new methods to suit with learners’ learning styles.